Learner Engagement in Using Kahoot! within a University English Proficiency Course - Mohd Zulfadli, Mat Husin; Ruhil Amal, Azmuddin (ÜNİVERSİTEPARK Limited, Istanbul, Turkey, 2022)
Background/purpose – Game-based learning is becoming increasingly popular among educators in higher institutions. However, it can be a daunting task for educators to ascertain which of the currently available game-based learning platforms best suits their learners’ needs. This study explored the suitability of Kahoot! as one of the most commonly used game-based learning platforms in education. The aim of study was to determine whether Kahoot! can be used to engage learners and reinforce learning for academic purposes in higher education institutions.